The Logic of Bureaucratic Conduct / An Economic Analysis of Competition, Exchange, and Efficiency in Private and Public Organizations - Breton Albert; Wintrose Ronald (Cambridge University Press, 1982)
Preface, Preliminary Survey, The Structure of the Model, Public and Private Policies, Economic and Accounting Budgets, The Interests of Bureaucrats, A Theory of Selective Behavior, The Cost of Public Policies, The Accumulation of Trust, A Digression Inspired by the Literature on Trust and Related Phenomena, The Compensation of Bureaucrats, Monopoly Models of Bureaucracy in the Public Sector, Selective Behavior and Managerial Competition, The Size Distribution of Bureaus, Schumpeterian Competition, The Allocation of Resources Among Bureaus, Some Applications, Organizational Structure and Productivity, Income and Price Controls, Parkinson's Law, Concluding Observations and Agenda, Departures, The Way Ahead, Notes, Index.